2006
DOI: 10.1080/09553000600579207
|View full text |Cite
|
Sign up to set email alerts
|

Study of the tools available in biological dosimetry to estimate the dose in cases of accidental complex overexposure to ionizing radiation: The Lilo accident

Abstract: It has been useful to compare cytogenetic results with clinical results. The results presented here reveal good stability of translocations. However the first dose estimation was not attempted until 6 months after the last exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…One particular aberration, a chromosomal translocation, appears so frequently that it can be used for dosimety purposes [65,66] and can be stable for months after the initial exposure [67]. Due to the overwhelming evidence that chromosomal translocations are a major component of the genome instability that promotes cellular dysregulation in many types of leukemias and lymphomas [20,68], it is clear that understanding how translocations form following irradiation is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…One particular aberration, a chromosomal translocation, appears so frequently that it can be used for dosimety purposes [65,66] and can be stable for months after the initial exposure [67]. Due to the overwhelming evidence that chromosomal translocations are a major component of the genome instability that promotes cellular dysregulation in many types of leukemias and lymphomas [20,68], it is clear that understanding how translocations form following irradiation is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…The fraction of exchanges detected was calculated using equations appropriate for one-to three-color paints [31] and was based on the DNA content of the painted chromosomes [32]. The proportion of genome coverage differs slightly for males and females due to the larger size of the X compared to the Y chromosome and some laboratories adjust for these gender differences in their calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Individual laboratories cultured the blood samples and painted various combinations of chromosomes according to their routine practices [10,15,[27][28][29][30][31][32][33][34][35]. The specific chromosomes that were painted and the number of colors used by each laboratory are shown in Table 1.…”
Section: Blood Sample Collection and Culture Methodsmentioning
confidence: 99%
“…Both models have been validated in vitro by mixing irradiated and unirradiated blood in different proportions [5]. These approaches have also been tested in vivo in accidental situations, with promising results [6,7]. Furthermore, recent in vivo studies of cancer patients who had received 8 Gy of radiotherapy in a single fraction have shown that the derived partial-body dose obtained with both Qdr and Dolphin methods are in agreement with the doses estimated from the radiotherapy regimens [8].…”
mentioning
confidence: 50%